Bridging Medicine and Literature in Anton Chekhov’s Short Fictional Works (Prithvi Journal of Research and Innovation, 2025)
This paper attempts to explore and analyze the medical issue and its effects on human relations as portrayed in literary writings. The paper is an interdisciplinary study of literature that deals with literature from the medical humanism perspective, connecting two diverse academic disciplines such as medicine and literature. For the theoretical perspective, it borrows the insights of Hulail and Charon, the theorists of medical humanities. In this paper, the characters who represent doctors and patients from the selected stories of Anton Chekhov are analyzed from the perspective of medical humanism, particularly the concept of narrative medicine developed by Hulail and Charon. The paper concludes that Chekhov’s works bridge the clinical science with literature through empathy, ethics, respect, and humanly behavior among sick people, with their illness and medication.